2020
DOI: 10.1002/cti2.1199
|View full text |Cite
|
Sign up to set email alerts
|

Influenza‐specific IgG1+ memory B‐cell numbers increase upon booster vaccination in healthy adults but not in patients with predominantly antibody deficiency

Abstract: Background. Annual influenza vaccination is recommended to all individuals over 6 months of age, including predominantly antibody deficiency (PAD) patients. Vaccination responses are typically evaluated by serology, and because PAD patients are by definition impaired in generating IgG and receive immunoglobulin replacement therapy (IgRT), it remains unclear whether they can mount an antigen-specific response. Objective. To quantify and characterise the antigen-specific memory B (Bmem) cell compartment in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 73 publications
0
37
0
Order By: Relevance
“…The proportion of RBD‐specific IgM or IgG Bmem cells in patients with COVID‐19 ranged from 4000 to 200 000 ASCs per 10 6 cells in the total B‐cell population. In other viral infections, comparable number of Bmem cells has been observed 35,41–43 …”
Section: Discussionmentioning
confidence: 65%
“…The proportion of RBD‐specific IgM or IgG Bmem cells in patients with COVID‐19 ranged from 4000 to 200 000 ASCs per 10 6 cells in the total B‐cell population. In other viral infections, comparable number of Bmem cells has been observed 35,41–43 …”
Section: Discussionmentioning
confidence: 65%
“…2 standard deviations (2SD) above the median of healthy controls ( Figure 2B and C ). All controls and patients had detectable levels of IgG to hemagglutinin (HA) of influenza H1N1 strain A/Michigan/45/2015 ( Figure 2D ) (Hartley et al, 2020), which was a recommended strain in the quadrivalent annual vaccine from 2017-2019 (Australian Immunisation Handbook, 2018). There was no significant difference in HA antibody levels between the patient and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…phycoerythrin (PE) and allophycocyanin (APC)) (Brouwer et al, 2020; Juno et al, 2020; Kaneko et al, 2020; Liu et al, 2019; Rodda et al, 2020; Wheatley et al, 2016; Zhou et al, 2020). To further overcome this limitation, we used non-protein polymer fluorochromes, which exhibited minimal non-specific B-cell binding and increased the sensitivity of our assay (Hartley et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows a summary of the conventional diagnostic method to respiratory diseases, and it is contrasted with the alternatives that could be evaluated by FCM. [D] AILRT Influenza [E] RT-PCR Lung exploration Cell maps to identify variations of PBMC based on [F] t-SNE analysis [62,66] Microsphere-based antibody assay [63,64] Hemagglutinin-specific memory B cells [65] SARS-CoV-2 [G] NAAT [E] RT-PCR Serological testing…”
Section: Advantages and Limitations Of Conventional Methods Comparedmentioning
confidence: 99%
“…Under influenza context, it has been suggested that the use of microsphere-based flow cytometry immunoassay allows the functional characterization of influenza viruses, although mAb recognizes virus proteins and distinguishes between the inactivated virus and influenza virions; moreover, using this tool also allows the functional assessment of relative receptor affinity [ 63 , 64 ]. Recently, through FCM, hemagglutinin-specific memory B cells that express IgG1 were identified in previously vaccinated healthy adults; this result provides alternatives to evaluate the immune response as a response to booster vaccination or as a complementary test to diagnosis [ 65 ].…”
Section: Use Of Flow Cytometry In the Diagnosis Of Respiratory Dismentioning
confidence: 99%